THE SUBSURFACE MODELING OF KARAHA-TELAGA BODAS GEOTHERMAL SYSTEM USING GRAVITY METHOD - YOSEPHIN NIM:12314024, MISSELA
Global energy crisis forces some countries, Indonesia included, to start using alternative energy. One of those alternative energy is geothermal energy. This energy is harmless to nature, so exploitation won't cause more damage to the environment. Indonesia which is located between three active tectonic plates, makes the potential of geothermal energy exploitation is very high. Gravity method is one of geophysical method which can be used in preliminary study of geothermal exploration because it can be used to model a geothermal system, comprised of different rock types which serves different functions in the system. The expected output of this research are a digital complete Bouguer anomaly map, regional and residual anomaly maps, and a geothermal system model based on forward modeling result. Data taken for research is the Print Complete Bouguer Anomaly Map of Karaha-Telaga Bodas Geothermal System from a survey conducted in 1997. The map is then modified so it can give out a digital complete Bouguer anomaly map. The following step is regional and residual anomaly separation using moving average method and spectral filtering method. Forward modelling is made based on geological information so the output can correlate with the actual condition as best as possible (background density = 2.3 g/cc). Based on forward modelling result, from North-South-oriented cross section, a separate granodiorite intrusion body under Karaha and Telaga Bodas is present, with density contrast of 0.5 g/cc and interpreted as the heat source of the system. Volcanic breccia with density contrast of 0.1 g/cc and 0.05 g/cc are suspected as the reservoir of the system. The fluids of the Karaha-Telaga Bodas Geothermal System are estimated to come from acid sulphate water and meteoric water entering from Telaga Bodas, as well as meteoric water entering from Karaha. There is an upflow in the South, Telaga Bodas.